Acesso e transparência ativa de informações e documentos do IFRS através da plataforma arquivística AtoM - Seiffert, Claudineli Carin (2019)
The Federal Institute of Rio Grande do Sul (IFRS) is an important educational institution for local and regional socioeconomic development that graduates and qualifies citizens to work professionally in various sectors of society. It has the education as main activity it has accumulated important documentary collection over the course of its 10 years. Thus, this research aimed at the development of a study that attempted to provide active transparency of the information and archival documents of IFRS for the citizens, specially the documents of the Internal Forum of Employees of the Rectory between 2015 to 2018. The study is justified by the need to provide greater visibility to the institution's archival heritage, thus complying with LAI through active transparency. In order to support the research objectives, we used theoretical references that deal with cultural patrimony and archival heritage, archival science, archival principles, classification and arrangement, archival description and its rules, the software ICA-AtoM (AtoM), dissemination and access and the national archive policy. The contextualization of the research involves the Federal Institutes of Education, Science and technology and their creation, the Federal Institute of Rio Grande do Sul and the Documentation Management Coordination of the institution and the Internal Forum of Employees of the Rectory. The research is applied, descriptive, qualitative and quantitative. From the used technical procedures, the research is characterized as a case study, based on bibliographical and documentary consultation. Data collection was performed through information available on websites, analysis of documents of the Institution, as well as clarifications by electronic mail of the National Archives. From the results of the research it was possible: to identify, in a minimalist view, the archive group of IFRS, which is an open record group with its sub-group, i.e., the Institution units; to identify all Campuses and Rectory as Custodian Entities of Archival Collections; to systematize the IFRS file fund and define its levels of description; implement AtoM as an archival institutional platform of access and active transparency of information and documents of IFRS. From the multilevel description, the information and documents were shared through the AtoM and the catalog of the file of the Internal Forum of Employees of the Rectory was elaborated as a research instrument, corroborating, therefore, with the access and active transparency of information and documents at IFRS.